Systemic inflammation and metabolic syndrome components in threshold/subthreshold posttraumatic stress disorder and food addiction in a Polish community sample - Monika M. Stojek; Marta Łukowska; Jagoda Różycka; Maryla Sokołowska; Joanna Zielińska; Ari Nowacki; Roksana Duszkiewicz; Anna Psurek; Vasiliki Michopoulos (European Journal of Psychotraumatology)
Background: Posttraumatic stress disorder (PTSD) is associated with metabolic syndrome and various addictive behaviours. Food addiction (FA) is associated with obesity, and individuals with PTSD have higher rates of FA than those without. It is unclear whether addictive-like eating patterns contribute to the metabolic dysfunction in PTSD.Objective: We examined the relative contributions of PTSD, FA, and sex – as well as their interactive effects – to the systemic inflammation (CRP) and metabolic syndrome components (MetS: waist circumference, glucose, triglycerides, HDL cholesterol, insulin) in a general population of the Upper Silesia region in Poland.Method: N = 187 participants (52.7% women) completed Yale Food Addiction Scale 2.0 (FA symptoms count), Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) semi-structured interview (PTSD or other trauma and stressor-related disorder (OTSR) diagnosis presence), anthropometric assessment, and phlebotomy in a fasted state.Results: A series of hierarchical linear regressions indicated that greater number of FA symptoms had a significant effect on greater waist circumference, while PTSD/OTSR diagnosis had a significant effect on higher insulin levels. Sex did not moderate these relationships.Conclusions: It appears that dysregulated eating patterns are associated with greater abdominal obesity, but not with metabolic dysfunction. PTSD/OTSR, but not FA, contributes to greater insulin levels. The average metabolic indices were within normal limits reflecting a non-clinical nature of the sample. Future longitudinal studies should examine whether detection of and intervention for PTSD/OTSR symptoms may be a strategy for preventing progression of metabolic dysfunction.